Analisis Postur Kerja Operator Pengecatan dalam Rangka Meminimalisir Dampak Gangguan Muskuloskeletal - Muhammad Yusuf; Cyrilla Indri Parwati (Universitas Sarjanawiyata Tamansiswa, 2022)
The painting operator activity is done manually. This painting activity is carried out in a specific position and is carried out continuously, causing musculoskeletal disorders. This study aims to determine the working posture of the painting operator using the OWAS, RULA, and REBA methods. Data collection was carried out by distributing Nordic Body Map questionnaires to operators with several complaints. OWAS and RULA methods were used to find and analyze operator behavior that could cause musculoskeletal disorders and injuries. The results of the OWAS calculation show that the risk level score is 2. At the same time, the RULA risk level score is 3. The analysis results show that several operator postures pose a musculoskeletal risk, so improvements must be made. Hopefully, this proposed improvement will help reduce the risk of musculoskeletal injuries